THE SPORT FUNCTION OF THE HUMAN RESOURCES MANAGEMENT WITH A SPECIAL REVIEW ON THE TRAINING TECNOLOGY - Đorđe Nićin; Vidosav Lolić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Human resources management in sport treats primarly the sport functions as the tasks of the increase of the training process, which implicitly brings to the high and reliable sport results. Training technology is the most responsible for the accomplishment of the high sport achievemens, but organized, planned, programmed, leaded, control led, and corrected by the experts, that is, by the team experts, at the head with a coach. The aim of the study is to, taking in to consideration all the sport and other functions of the human resource management, analyze participation and importance of the training technology in the creation of a sportsman and in maintaining of his resources, to achieve great probability in achieving stable sport results, that is, maintaining sport form.